The Human Nature of Music - Malloch, Stephen; Trevarthen, Colwyn (Frontiers in Psychology, 2018)
Music is at the centre of what it means to be human – it is the sounds of human bodies and minds moving in creative, story-making ways. We argue that music comes from the way in which knowing bodies (Merleau-Ponty) prospectively explore the environment using habitual 'patterns of action' which we have identified as our innate ‘communicative musicality’. To support our argument, we present short case studies of infant interactions using micro analyses of video and audio recordings to show the timings and shapes of intersubjective vocalisations and body movements of adult and child while they improvise shared narratives of meaning. Following a survey of the history of discoveries of infant abilities, we propose that the gestural narrative structures of voice and body seen as infants communicate with loving caregivers are the building blocks of what become particular cultural instances of the art of music, and of dance, theatre and other temporal arts. Children enter into a musical culture where their innate communicative musicality can be encouraged and strengthened through sensitive, respectful, playful, culturally informed teaching in companionship. The central importance of our abilities for music as part of what sustains our well-being is supported by evidence that communicative musicality strengthens emotions of social resilience to aid recovery from mental stress and illness. Drawing on the experience of the first author as a counsellor, we argue that the strength of one person’s communicative musicality can support the vitality of another’s through the application of skilful techniques that encourage an intimate, supportive, therapeutic, spirited companionship. Turning to brain science, we focus on hemispheric differences and the affective neuroscience of Jaak Panksepp. We emphasise that the psychobiological purpose of our innate musicality grows from the integrated rhythms of energy in the brain for prospective, sensation-seeking affective guidance of vitality of movement. We conclude with a Coda that recalls the philosophy of the Scottish Enlightenment, which built on the work of Heraclitus and Spinoza. This view places the shared experience of sensations of living – our communicative musicality – as inspiration for rules of logic formulated in symbols of language.